Estudo sobre a necessidade e preferência sobre orientações de enfermagem ao paciente oncológico adulto em quimioterapia - Iamonti, Tatiana Chiaramonti [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Most cancer types are treated by antineoplastic chemotherapy, which can be performed conjointly with other treatments, such as radiotherapy and surgery. Due to its action, chemotherapy provides the possibility of cure, but it also leads to a number of adverse effects, such as myelosuppression, cutaneous and gastrointestinal toxicity, etc. Patients undergoing chemotherapy must receive constant information concerning how to prevent or minimize these effects in order to achieve better quality of life and, consequently, a more successful treatment. Hence, this study aimed at investigating the need and preference for different forms of information by oncologic patients submitted to chemotherapy. It is a cross-sectional, descriptive and quantitative study conducted at the chemotherapy division of the Botucatu School of Medicine University Hospital/SP on a sample of 50 patients older than 18 years. After previous knowledge of the study and formalization of Free Consent, the individuals answered a questionnaire containing 12 questions related to the importance attributed to the information received, from which professional and when to receive it. Data were analyzed by Fisher’s exact test and showed that 62% of the patients were females, and the remaining 38% were males of whom 46% were older than 60 years, 26% were from 50 to 60 years old, 24% from 30 to 50, and only 4% were younger than 30 years old. The patients had lymphatic (23.4%) and solid (76.6%) tumors. All the respondents reported that receiving information about the disease and its treatment was extremely important. As regards information related to side effects, 98% of patients answered that receiving it was extremely important, and only 2% answered that it was little important. Correlations were made between age, gender, and tumor type with the answers obtained for the best moment, how and from whom to receive such informatio... (Complete abstract click electronic access below)

A maioria dos cânceres é tratada a partir da quimioterapia antineoplásica. Ela pode ser realizada em concomitância a outros tratamentos como a radioterapia, cirurgia. A quimioterapia, pela sua ação, trás a possibilidade de cura, mas também uma série de efeitos adversos, como: mielossupressão, toxicitade cutânea, gastrointestinal, etc. Os pacientes em quimioterapia devem receber informações constantes a cerca desses efeitos, como prevení-los, ou minimizá-los para ter maior qualidade de vida e conseqüente maior sucesso no tratamento. Desta forma, objetivou-se neste estudo investigar a necessidade e a preferência pelas diferentes formas de informação junto aos pacientes oncológicos submetidos à quimioterapia. Este é um estudo transversal e descritivo, com abordagem quantitativa, realizado na seção de quimioterapia do Hospital das Clínicas do Município de Botucatu/SP, com uma amostra de 50 pacientes em idade superior a 18 anos. Após prévio conhecimento do estudo e formalização do Termo de Consentimento Livre e Esclarecido, os indivíduos responderam um questionário contendo 12 questões acerca da importância atribuída à informação recebida, por qual profissional e quando recebê-la. Os dados foram analisados através do teste exato de Fisher, evidenciaram que 62% dos pacientes eram mulheres e os outros 38% eram homens, 46% dos tinham mais que 60 anos, 26% tinham entre 50 e 60, 24% entre 30 e 50 anos e somente 4% tinham menos que 30 anos. Os pacientes eram portadores de tumores linfáticos (23,4%) e sólidos (76,6%). Todos entrevistados responderam que é extremamente importante receber informações sobre a doença e sobre o tratamento. Em relação às informações sobre os efeitos colaterais, 98% dos pacientes responderam ser extremamente importante receber essas informações e apenas 2% responderam ser pouco importante. Foram realizadas correlações... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Enfermagem; Quimioterapia; Câncer – Enfermagem